Analisis Kualiatas Pelayanan, Fasilitas, dan Promosi yang Mempengaruhi Kepuasan Pelanggan Pada The Garuda Homestay Sanur - Mahendra, I Putu Gede Andre Krisna; Suryathi, Wayan; Ritasintadevi, Ni Putu (Innovative: Journal Of Social Science Research, 2024)
The need for hotel accommodation is increasing, and one of the provinces in Indonesia that is famous for its tourism sector is Bali. However, as a result, there is now increasingly tight competition between accommodations. To improve customer satisfaction, all companies operating in this sector must choose the most appropriate approach. This study seeks to determine whether client happiness at The Garuda Homestay Sanur is directly influenced by the quality of service, facilities, and promotions. The questionnaire method was used in this study to collect data. In this study, data were collected by the questionnaire approach. Using a purposive sampling technique, 76 guest respondents who had stayed at The Garuda Homestay Sanur made up the suitable sample size. The data analysis methods that were employed included determination, t, f tests, reliability, validity, and multiple linear regression analysis. The results of the study demonstrated that: (1) a significant partial effect of 0.000 was found for service quality; (2) a significant partial effect of 0.000 was found for facilities; (3) a significant partial effect of 0.000 was found for promotion; and (4) a significant simultaneous effect of 0.000 was found for service quality, facilities, and promotion on customer satisfaction.